Les stratégies de recherche d’aide des femmes victimes de violence conjugale : le cas des femmes référées aux CLSC par les policiers - Rinfret-Raynor, Maryse; Cantin, Solange; Fortin, Lise (Criminologie, 1997)
This article deals with formal and informal resources used by women victims of conjugal violence in their search for help. It explores the type of resources used and their relationship with a number of factors such as the socio-economic characteristics of the women and, the nature and duration of the violence which they have suffered. Prior to reporting on the results of a specific case of formal resources utilization, this article presents a review of the literature on the process of seeking help, then it focuses on the major role played by the social support network. Also, it reviews the major studies dealing with the strategies used by women victims of conjugal violence in obtaining help. Finally, the article reports on the main results of a study conducted in the context of a pilot project to bring help to victims of conjugal violence by the police and the Local Community Services Centers (CLSC) of the Montreal Urban Community. This pilot project started in 1990 has since been extended to the entire territory covered by the Montreal Urban Community. The results of this study show that the majority of the women referred by the police officers did receive help at the CLSC. However, only one third of the women referred did meet with a social practioner following the referral. Also, it was observed that when the period between the referral and the first contact by the social practitioner was short, the women more easily accepted to meet with a worker from the CLSC. A third of the women referred already had a file with the CLSC, which indicated that the violence problem was known in one case out of four. Meeting with a CLSC worker was found to provide a greater diversity in the type of help received.